Pengembangan Media Pembelajaran Berbasis Aplikasi Android Pada Pembelajaran IPA Kelas V Sekolah Dasar - Karlina Amelia Djaelani (STKIP Melawi, 2022)
The purpose of this development is to produce a product of Android-Based Learning Media on Water Cycle Material Science Learning that is valid and effective. This development has gone through several stages, namely the stages of needs analysis, design, development, implementation, and evaluation in accordance with the development model. Product validation was carried out to media experts, material experts, and instructional experts. The target of the trial was the fifth grade elementary school students. Based on validation trials conducted by media experts, the media validity level is 85%. Trials by material experts get a validity level of 97.5%. The trial by instructional experts got a validity level of 88.3% and the validity level of students was 81.75%, it was concluded that the learning media developed was included in the valid and effective category in learning activities.